Surface Active Monomers Synthesis, Properties, and Application - Borzenkov, Mykola (Springer eBooks, 2014)
This brief includes information on the background of and development of synthesis of various types of surface active monomers. The authors explain the importance of utilization of surface active monomers for creation of surface active polymers  and the various biomedical applications of such compounds . This brief introduces techniques for the synthesis of novel types of surface active monomers, their colloidal and polymerizable properties and application for needs of medicine and biology.